Akad pada Sistem Marketing Halal Network International (HNI) Perspektif Fikih Muamalah (Studi Kasus Agency Center HNI di Dusun Made, Gabus, Ngrampal, Sragen) - Dwi Artiningsih; Luthfiana Zahriani; Asiah Wati (JES (Jurnal Ekonomi Syariah), 2023)
This study aims at determining the marketing system and analyzing contracts in Halal Network International marketing system at the Gabus Agency Center, Ngrampal, Sragen based on the perspective of muamalah fiqh. This qualitative field research obtains the primary data through interviews using the purposive sampling method, namely HNI Agency Center owners in Gabus, Ngrampal, Sragen, HNI Sharia Supervisory Board (DPS) and HNI agents or consumers shopping at HNI Agency Centers. While secondary data comes from books, journals, theses and the internet related to contracts in the Halal Network International marketing system from the perspective of fiqh muamalah. Data collection techniques are by means of interviews, observation and documentation. While the data analysis technique uses the Milles and Huberman method, namely collecting data, data reduction, data presentation and conclusions. The results of the study show that the marketing system used in HNI at the Agency Center Made, Gabus, Ngrampal Sragen is the Sharia Network Marketing (MLM Syariah) system, namely marketing products through a network of agents using the DSN/MUI Fatwa reference No.75/DSN-MUI/VII /2009 concerning Guidelines for Sharia Tiered Direct Sales (PLBS). Contracts in HNI marketing system from a muamalah fiqh perspective between HNI companies and the Agency Center Made, Gabus, Ngrampal, Sragen use ju'alah contract and wakalah bil ujrah contract. Meanwhile, at the Agency Center Made, Gabus, Ngrampal, Sragen with HNI agents or consumers, in selling HNI products, they use murabahah and salam contracts.